Answer:
(a - b)(5x - 2y)
Step-by-step explanation:
5x(a - b) – 2y(a - b) =
The factors in parentheses (shown in bold) are a common factor.
Factor (a - b) out from both terms.
= (a - b)(5x - 2y)
The function A(x) = 2x²-3x-2 represents the area of the garden.
Step-by-step explanation:
Given,
Length of rectangular garden is given by;
L(x) = 2x+1
Width of rectangular garden is given by;
W(x) = x-2
Area of rectangular garden;
A(x) = L(x) * W(x)
![A(x) = (2x+1)(x-2)\\A(x) = 2x(x-2)+1(x-2)\\A(x) =2x^2-4x+x-2\\A(x) = 2x^2-3x-2](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%282x%2B1%29%28x-2%29%5C%5CA%28x%29%20%3D%202x%28x-2%29%2B1%28x-2%29%5C%5CA%28x%29%20%3D2x%5E2-4x%2Bx-2%5C%5CA%28x%29%20%3D%202x%5E2-3x-2)
The function A(x) = 2x²-3x-2 represents the area of the garden.
Keywords: Area, rectangle
Learn more about area at:
#LearnwithBrainly
Step-by-step explanation:
![{2}^{2} + {x}^{2} = {6}^{2} \\ 4 + {x}^{2} = 36 \\ {x}^{2} = 36 - 4 \\ {x}^{2} = 32 \\ x = \sqrt{32}](https://tex.z-dn.net/?f=%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20%3D%20%20%7B6%7D%5E%7B2%7D%20%20%5C%5C%204%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20%3D%2036%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%3D%2036%20-%204%20%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20%3D%2032%20%5C%5C%20x%20%3D%20%20%5Csqrt%7B32%7D%20)
hope u get it. I've used RHS to prove LHS